2019
DOI: 10.1089/pop.2018.0016
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Disorders and Medical Complications Among Infants with Subclinical Intrauterine Opioid Exposures

Abstract: The objective was to compare diagnosis rates representing developmental outcomes and medical complications between infants with intrauterine opioid exposures who did not receive pharmacologic treatment for neonatal abstinence syndrome at the time of birth and infants for whom no exposure to substances of abuse were detected. This retrospective, descriptive study included approximately 95% of Hamilton County, Ohio resident births in 2014 and 2015. Universal maternal drug test results, performed at the time of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 29 publications
2
29
0
Order By: Relevance
“…However, four studies found significantly higher rates of hospitalizations for exposed children through the first 5 years of life (Kelty & Hulse, 2017; Skurtveit et al, 2019; Uebel et al, 2015; Witt et al, 2017). Five studies examined morbidities using ICD codes (Hall, McAllister, & Wexelblatt, 2019; Kelty & Hulse, 2017; Skurtveit et al, 2019; Uebel et al, 2015; Witt et al, 2017), and found significantly higher morbidity among exposed children through the first 2, 3, 5, and 13 years of life, including diagnoses of infections and parasitic diseases, diseases of the digestive system, and diseases of the skin and subcutaneous tissue across all studies. Three studies (Kivistö, Tupola, & Kivitie‐Kallio, 2015; Uebel et al, 2015; Witt et al, 2017) also found significantly higher rates of abuse, neglect, and maltreatment in exposed children compared with unexposed children.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, four studies found significantly higher rates of hospitalizations for exposed children through the first 5 years of life (Kelty & Hulse, 2017; Skurtveit et al, 2019; Uebel et al, 2015; Witt et al, 2017). Five studies examined morbidities using ICD codes (Hall, McAllister, & Wexelblatt, 2019; Kelty & Hulse, 2017; Skurtveit et al, 2019; Uebel et al, 2015; Witt et al, 2017), and found significantly higher morbidity among exposed children through the first 2, 3, 5, and 13 years of life, including diagnoses of infections and parasitic diseases, diseases of the digestive system, and diseases of the skin and subcutaneous tissue across all studies. Three studies (Kivistö, Tupola, & Kivitie‐Kallio, 2015; Uebel et al, 2015; Witt et al, 2017) also found significantly higher rates of abuse, neglect, and maltreatment in exposed children compared with unexposed children.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies (Gill et al, 2003; Hall et al, 2019; Hamilton et al, 2010; Uebel et al, 2015) examined vision in children with in‐utero opioid exposure using ophthalmology assessment and ICD code analysis. All studies reported increased incidence of visual disorders, specifically strabismus and nystagmus in children with in‐utero opioid exposure.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 5865 titles identified from searches, 581 full texts were assessed for eligibility, 15 eligible studies were identified, and six were amenable to meta-analysis (Figure 2). (11,(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42) This represented 10,907 children with a history of NAS and 1,730,213 unexposed children (Table 5; available at www.jpeds.com). (11,(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42) Multiple publications from the same cohort were clarified, to avoid duplication of cases in the statistical analysis.…”
Section: Resultsmentioning
confidence: 99%
“…(30-32, 34, 38, 41) Eight studies were deemed to be overall good quality, (11,(32)(33)(34)(35)(36)(37)39) 4 were deemed fair, (29)(30)(31)41) and three poor (Table 6; available at www.jpeds.com). (38,40,42) Included studies were published between 2003-2019 with infants born between 1998 and 2016. (11,(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42) The age range of included children was 0-16 years; ages for specific outcome assessments often were not provided (Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…Our survey highlighted several knowledge gaps: (1) the variation across pediatric subspecialty in inpatient and post-discharge referral practices for infants with NAS, (2) the lack of follow-up for infants with NAS-No-Tx compared with NAS-Tx despite a similar risk of long-term complications in both groups [3], and (3) the short duration of follow-up for infants with NAS, raising concerns in light of the widening disparity and challenges for this population over time [4]. The low response rate in our study may reflect unfamiliarity with post-discharge practices among respondents.…”
Section: To the Editormentioning
confidence: 99%